Förster resonance energy transfer properties of a new type of near-infrared excitation PDT photosensitizer: CuInS2/ZnS quantum dots-5-aminolevulinic acid conjugates. Issue 60 (9th June 2016) - Feng, Yueshu; Liu, Liwei; Hu, Siyi; Liu, Yingyi; Ren, Yu; Zhang, Xihe
Abstract : Recently, near-infrared (NIR) excitation has been suggested for PDT improvement and therapy of cancer. Abstract : Recently, near-infrared (NIR) excitation has been suggested for PDT improvement and therapy of cancer. In this study, 5-aminolevulinic acid (ALA), a photosensitizer used for photodynamic therapy (PDT) of cancer, was coordinated to CuInS2 /ZnS (CIS/ZnS) QDs to form CIS/ZnS–ALA conjugates, by chemical bonding. An efficient transfer of energy from the donor (QDs) to the acceptor (ALA) was demonstrated through Förster resonance energy transfer (FRET), and the FRET efficiency of QDs–ALA system can reach as high as 58.49% under near-infrared excitation. The optical properties (fluorescence spectra, Fourier transform-infrared spectra and fluorescence lifetimes) were also determined for the conjugates. In addition, the PDT killing in vitro was further achieved under the 800 nm and 1300 nm femtosecond laser pulses. These results demonstrate that the CIS/ZnS–ALA conjugates are promising for PDT and needed to be investigated further.